Applications to augment patient care for Internal Medicine specialists: a position paper from the EFIM working group on telemedicine, innovative technologies & digital health - Pietrantonio, F.; Florczak, M.; Kuhn, S.; Kärberg, K.; Leung, T.; Said Criado, I.; Sikorski, S.; Ruggeri, M.; Signorini, A.; Rosiello, F.; Drago, C.; Vinci, A.; et al. (Frontiers in Public Health, 2024)
Telemedicine applications present virtually limitless prospects for innovating and enhancing established and new models of patient care in the field of Internal Medicine. Although there is a wide range of innovative technological solutions in Europe, there are overarching elements associated with such technologies when applied to the practices of Internal Medicine specialists. The European Federation of Internal Medicine (EFIM) strongly advocates for active leadership and influence from the Internal Medicine societies and specialist physicians across Europe in the development and application of telemedicine and digital technologies in healthcare. This position paper’s conclusions were drawn via Delphi method, which was developed collaboratively from July 2021 to December 2023. The panel, consisting of experts in clinical medicine, public health, health economics and statistics, assessed various aspects related to telemedicine. Participants assigned scores on a Likert scale reflecting perceived value and potential risks. The findings were consolidated in a comprehensive checklist aligning with relevant literature and a SWOT analysis. Specifically, key issues that need to be addressed include promoting the professional development of e-health competencies in the healthcare and medical workforce, using educational campaigns to promote digital literacy among patients and caregivers, designing and implementing telemedicine applications tailored to local conditions and needs and considering the ethical and legal contexts under which these applications are employed. Importantly, there is currently no consensus on care models or standardized protocols among European Internal Medicine specialists regarding the utilization of telemedicine. This position paper aims to outline the opportunities and challenges associated with the application of telemedicine in Internal Medical practice in Europe.